Asset-Based Vs Deficit-Based Esl Instruction: Effects On Elementary Students Academic Achievement And Classroom Engagement - Arslan Asad Chaudhary (Migration Letters, 2022)
This paper aims to establish that academic achievement and classroom engagement are useful components of educating elementary students, with a focus on ESL learners. English is not the native language in many areas, particularly in Asian countries, and that is why the proper implementation of ESL is crucial. Regarding the previous literature, this research aims to compare and contrast the impact of asset-based and deficit-based ESL instruction and their[1] consequences on students’ successes and participations. Using a cross-sectional method with participants from Hanoi and Huế in Vietnam. The study included 300 participants. The results of the statistical analyses showed high alpha reliability in the sample, suggesting high internal consistency and reliable scores. The findings indicated that asset-based ESL instruction was positively associated with students’ academic performance and active participation in the classroom. On the other hand, a negative correlation between deficit-based ESL instruction and the above outcomes is observed. An analysis of a regression model is conducted, and it supported the fact that asset-based instruction had a positive effect on students’ achievement and their attitudes. The study also revealed these gender and provincial differences in the inter-correlations among the variables. This research highlights the need for developing asset-based instructional practices for boosting academic achievement and student interest in the ESL context, which can help educators and policymakers in framing effective teaching and learning methods that will address the needs of all boys and girls.